Prioritizing non-fatal occupational injury prevention using risk matrix assessment among palm oil mills’ workers - Ruslan, Rumaizah; Baba, Ishak (Science & Engineering Research Support Society (SERSC), 2020)
Non-fatal occupational injury (NFOI) had becoming a major global concern and its consequences to safety and health would be heavily burdening. The aim of this paper is to assess the risk rating of occupational injury among workers in palm oil mills in order to identify preventive effort that most needed for specific workstation in mill. The NFOI data was gathered via questionnaire among 66 palm oil mills’ workers who reported to had experienced injuries while working. Risk matrix tool was utilized for non-fatal occupational injury risk assessment and prevention. The risk rating of occupational injury was obtained by employing standardized equation involving probability unit and severity unit. The risk rating was categorized as low, moderate, high and subsequently preventive measurements were suggested based on the priority. The highest cases of non-fatal occupational injury were reported to occur at Press Plant (19%) with moderate risk rating. Falling incidences had the highest frequency of occurrences among workers in palm oil mills. The frequent type of injury reported by palm oil mills’ workers was minor cuts and scratches (43%). The risk rating of reported non-fatal occupational injury at palm oil mills was in moderate level. Therefore, directive control and detective control could be proposed as the risk control for workers in palm oil mills. By utilizing risk matrix tools, the intervention needs and priority toward injury prevention among workers in palm oil mills could be determined.